Evaluation of digestion procedures in Kjeldahl method to quantify total nitrogen in analyses applied to animal nutrition - Silva, Tadeu Eder da; Detmann, Edenio; Franco, Marcia de Oliveira; Palma, Malber Nathan Nobre; Rocha, Gabriel Cipriano (Acta Scientiarum. Animal Sciences, 2016)
The effects of the salt-to-metal catalyst ratio and amount of digestion mixture on total nitrogen content in different materials using the Kjeldahl method were evaluated. Four samples with low nitrogen contents and four samples with high nitrogen contents were analyzed. The study evaluated two ratios of salt (sodium sulfate) to metal catalyst (copper sulfate) in the digestion mixture (10:1 and 20:1) and three amounts of digestion mixture per sample (1.0, 1.5, and 2.0 g 200 mg-1). There was an interaction between low-nitrogen material and amount of digestion mixture on nitrogen contents. Samples of cattle feces and corn presented higher nitrogen content when 1.5 and 2.0 g of digestion mixture were used. The high-nitrogen materials presented higher nitrogen contents when 2.0 g of the digestion mixture was used. However, there was an interaction between high-nitrogen material and the ratio of the digestion mixture components. The cattle carcass sample showed higher nitrogen content when the 20:1 ratio was used. The digestion mixture amount in the Kjeldahl method must be 2.0 g with a salt-to-metal catalyst ratio of 20:1 when samples of approximately 200 mg are analyzed.